PENGARUH MODEL PEMBELAJARAN PROBLEM CENTERED LEARNING TERHADAP KETERAMPILAN KOMUNIKASI INTEPERSONAL SISWA KELAS IV UPT SPF SD NEGERI BORONG - Siti Raihan; Nurhaedah; Nur Muthmainnah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the application of the Problem Centered Learning learning model, find out the interpersonal communication skills of students and find out the influence of the Problem Centered Learning learning model on the interpersonal communication skills of grade IV students of UPT SPF SD Negeri Borong. This study uses a quantitative approach with a quasi-experimental design. The subject of the study involved 53 students in grade IV of elementary school, consisting of 27 students in the experimental class and 26 students in the control class using the purposive sampling method. The research instrument consists of observation sheets and questionnaires. The data collection procedures, namely pre-nontest, treatment, and post-nontest, were then analyzed by descriptive statistics and inferential statistics. The results of this study show that: (1) the application of the Problem Centered Learning learning model that was carried out obtained a good category with 3 stages individual problem-solving activities.